2020
DOI: 10.1098/rstb.2019.0690
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the neural basis of fear produced by mental imagery: imaginal exposure in individuals fearful of spiders

Abstract: Imaginal exposure, i.e. reducing fear using exposure to mental imagery, is a widely used psychological treatment technique for dysfunctional fears. Yet, little is known about its underlying neural mechanisms. The present study examines the neural basis of imaginal exposure using a novel experimental procedure consisting of repeated exposure to flashpoint mental imagery of phobic (spiders) and neutral (gloves) stimuli. Whether the 10 min long imaginal exposure procedure could reduce fear responses was examined … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
20
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(24 citation statements)
references
References 57 publications
1
20
0
3
Order By: Relevance
“…Furthermore, mental imagery is not restricted to sensory experiences, but can also involve simulating motion and motor behavior. Just as producing mental imagery of an object, and seeing the same object (e.g., a spider), recruit similar neurocircuitry and have a similar impact on emotion (Hoppe et al, 2021;Pearson, 2019), so does imagining and executing a motor action (e.g., running; Munzert et al, 2009). It has been suggested that interference tasks need to be in the same modality as the targeted imagery to be effective (e.g., visuospatial task to target visual mental imagery; Baddeley & Andrade, 2000).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Furthermore, mental imagery is not restricted to sensory experiences, but can also involve simulating motion and motor behavior. Just as producing mental imagery of an object, and seeing the same object (e.g., a spider), recruit similar neurocircuitry and have a similar impact on emotion (Hoppe et al, 2021;Pearson, 2019), so does imagining and executing a motor action (e.g., running; Munzert et al, 2009). It has been suggested that interference tasks need to be in the same modality as the targeted imagery to be effective (e.g., visuospatial task to target visual mental imagery; Baddeley & Andrade, 2000).…”
Section: Discussionmentioning
confidence: 99%
“…Exclusion criteria consisted of current psychiatric disorder (other than spider phobia), substance abuse, neurological disease, receiving psychological treatment or psychotropic medication within six months, and contraindications for magnetic resonance imaging. Data was collected as part of an unrelated experiment where one of the inclusion criteria was fear of spiders (Hoppe et al, 2021). Twenty-eight participants (age: M = 23.8, SD = 5.8 years, 7 men and 21 women) were included in analyses.…”
Section: Participantsmentioning
confidence: 99%
See 1 more Smart Citation
“…Finally, the null effect of vividness could indicate that imagery specifically does not give rise to the mood amplification effects in our study, and instead the task acts more as a general mood induction procedure. This explanation seems unparsimonious given evidence that mental imagery accompanies sensory perception and stimulus-independent processing, and its generation alters affective states across a variety of populations Hoppe et al, 2021;Kessler et al, 2018;. We suggest that future studies further explore the role of vividness using an expanded operating range for vividness scores and converging behavioural and neurophysiological imagery markers (Cui et al 2007;Pearson et al, 2015).…”
Section: No Effect Of Vividness [H3]mentioning
confidence: 93%
“…Over and above the general relevance research on different forms of self-generated mental phenomena might have for advancing our understanding of clinical conditions and shaping approaches to their treatment, certain forms of self-generated experiences can have direct benefit in psychological treatment. In the fourteenth paper of this issue, Hoppe et al [67] present findings with regard to how mental imagery can be used in the treatment of phobic fear, and explore the possible link between the neural mechanisms underlying online fear-processing and generating a mental image of a phobic stimulus.…”
Section: The Topics Of the Theme Issuementioning
confidence: 99%